2015
DOI: 10.1111/are.12744
|View full text |Cite
|
Sign up to set email alerts
|

Cajeput oil, an effective botanical against gyrodactylid infection

Abstract: Infectious diseases are a major welfare issue, economically costly and, from a conservation perspective, threaten susceptible fish populations. Parasite control in aquaculture is over reliant on a limited range of treatments which tend to be low in efficacy, toxic to hosts and have negative consequences on human health and the environment. Here, we tested 22 botanical treatments alongside five controls against Gyrodactylus turnbulli (Harris 1986), in vitro and in vivo, infecting guppies (Poecilia reticulata Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The continued pursuit to optimise aquatic parasite culture techniques will enable researchers In vitro and in vivo monogenean cultures have been used to examine the efficacy of commercial [91] and natural products [17,92,93] as well as biocontrols [94]. In vivo culture enabled parasite life cycle parameters to be examined in response to varied environmental parameters which were used to develop strategic treatment regimens on aquaculture farms [10,74].…”
Section: Discussionmentioning
confidence: 99%
“…The continued pursuit to optimise aquatic parasite culture techniques will enable researchers In vitro and in vivo monogenean cultures have been used to examine the efficacy of commercial [91] and natural products [17,92,93] as well as biocontrols [94]. In vivo culture enabled parasite life cycle parameters to be examined in response to varied environmental parameters which were used to develop strategic treatment regimens on aquaculture farms [10,74].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cajuput applied with Tween 20 was nearly as effective as the Melafix ® /Pimafix ® combination with approximately 90% ef ficacy using G. turnbulli infecting gup pies (Poecilia reticulata) (see Schelkle et al 2015). The longer dur ation of exposure and a lower dose of the cajuput treatment in the current study increased the efficacy to 95%.…”
Section: Discussionmentioning
confidence: 53%
“…By preparing the mixture in the laboratory, the compounds may have been affected by light degradation or oxidation processes which, in turn, may have affected treatment efficacy. Finally, seeing that cajuput has previously been shown to be highly anti-parasitic (Schelkle et al 2015), a double dose of Melafix ® by itself may be equally as effective as the combination treatment used in the current study; however, such speculation would have to be confirmed through further testing.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations